The relationship between digital and scientific literacy with biology cognitive learning outcomes of high school students - Andi Muhamad Yusuf; Dian Tauhidah; Saifullah Hidayatullah (Assimilation: Indonesian Journal of Biology Education, 2022)
Digital literacy and scientific literacy are needed in the world of education as an effort to make students have 21st century competencies. This study aims to determine the relationship between digital literacy and scientific literacy together with cognitive biology learning outcomes of SMA N 16 Semarang students during the COVID-19 pandemic. This research is correlational quantitative research. The population of this study were students of class XI SMAN 16 Semarang with a total of 108 students. Sampling technique was using saturated sampling. Data collecting techniques were using questionnaires for digital literacy variables and tests for scientific literacy and cognitive biology learning outcomes. Hypothesis testing was using multiple correlation. The results showed that there was a positive and significant relationship between digital literacy and scientific literacy with cognitive biology learning outcomes, with a significance value of 0.00 ˂ 0.05, a large correlation value of 0.474 (medium correlation), and a coefficient of determination of 20.4%. It is important for teachers and students to apply digital literacy and scientific literacy to improve cognitive learning outcomes.